A new species Danaea (Marattiaceae) from the Atlantic forests of Brazil - Christenhusz, Maarten J. M.; Almeida, Erton M.; Felix, Leonardo P. (Phytotaxa, 2018)
With a long fossil history (Taylor, Taylor & Krings 2009), Marattiaceae are among the earliest lineages of vascular land plants and are an important link to understanding land plant evolution. The family currently has a pantropical distribution, but was more widely distributed in the past. In the neotropics the family is represented by the genera Marattia Swartz (1788: 128), Eupodium Smith (1841: 190) and Danaea Smith (1793: 420). An additional three genera are found in the paleotropics and in total the family has an estimated 135 known species (Christenhusz & Byng 2016).